Criminal Law Enforcement Against Cyber Phising Perpetrators (Study of decision Number 85/Pid.Sus/2022/PN Bjb) - Harahap, Amalia Zahra; Marpaung, Zaid Alfauza (IHSA Institute, 2024)
Cyber ??phishing crimes are the result of technological advances that allow attacks without physical interaction. This problem is getting worse and is a serious threat to public safety. This study examines the phenomenon of theft and hacking of personal data in a digital context, especially related to cyber phishing violations. This study also evaluates the criminal law framework in Indonesia that regulates these crimes. The methodology used is normative law with a conceptual approach, namely analyzing written laws from library materials, and collecting data from academic literature. The analysis in this study refers to the provisions of the applicable laws. This study aims to determine how criminal law applies to phishing perpetrators in decision No.85/Pid.Sus/2022/PN.Bjb and, explore the relationship between this problem and the Criminal Code, Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions and the Personal Data Protection Law. The results of the study discuss how the criminal law system deals with cybercrimes such as phishing, to overcome this crime problem, it is important to increase public awareness, provide education, and strengthen personal data security.